Model-Based Experimental Development of Passive Compliant Robot Legs from Fiberglass Composites. (1st June 2015) - Lin, Shang-Chang; Hu, Chia-Jui; Shih, Wen-Pin; Lin, Pei-Chun
Abstract : We report on the methodology of developing compliant, half-circular, and composite robot legs with designable stiffness. First, force-displacement experiments on flat cantilever composites made by one or multifiberglass cloths are executed. By mapping the cantilever mechanics to the virtual spring model, the equivalent elastic moduli of the composites can be derived. Next, by using the model that links the curved beam mechanics back to the virtual spring, the resultant stiffness of the composite in a half-circular shape can be estimated without going through intensive experimental tryouts. The overall methodology has been experimentally validated, and the fabricated composites were used on a hexapod robot to perform walking and leaping behaviors.